2011 International Conference on Machine Learning and Cybernetics 2011
DOI: 10.1109/icmlc.2011.6016982
|View full text |Cite
|
Sign up to set email alerts
|

Channel pattern noise based playback attack detection algorithm for speaker recognition

Abstract: This paper proposes a channel pattern noise based approach to guard speaker recognition system against playback attacks. For each recording under investiga tion, the channel pattern noise severs as a unique chan nel identification fingerprint. Denoising filter and statis tical frames are applied to extract channel pattern noise, and 6 Legendre coefficients and 6 statistical features are extracted. SVM is used to train channel noise model to judge whether the input speech is an authentic or a play back recordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(41 citation statements)
references
References 5 publications
1
40
0
Order By: Relevance
“…Such algorithms were reported in [37], for which the EER of a baseline GMM-UBM system was shown to decrease from 40 % to 10 % with active countermeasures. Another replay countermeasure aimed at detecting far-field recordings, which are unlikely in natural access scenarios where the speaker is usually close to the microphone [36].…”
Section: Spoofing Countermeasures For Asv Systemsmentioning
confidence: 99%
“…Such algorithms were reported in [37], for which the EER of a baseline GMM-UBM system was shown to decrease from 40 % to 10 % with active countermeasures. Another replay countermeasure aimed at detecting far-field recordings, which are unlikely in natural access scenarios where the speaker is usually close to the microphone [36].…”
Section: Spoofing Countermeasures For Asv Systemsmentioning
confidence: 99%
“…A physical access scenario was considered in (Wang et al, 2011). Although no baseline statistics were reported, a textindependent GMM-UBM system was shown to give an EER of 40.17 % when subjected to replay attacks.…”
Section: Spoofingmentioning
confidence: 99%
“…Recently, due to the mass-market adoption of ASV techniques Nuance, 2013) and the awareness and simplicity of replay attacks, both industry (Nuance, 2013) and academia (Shang and Stevenson, 2010;Villalba and Lleida, 2011a,b;Wang et al, 2011) have shown an interest in developing replay attack countermeasures.…”
Section: Countermeasuresmentioning
confidence: 99%
“…In the literature, detection of replay attacks has largely focused on characteristics related to channel noise and reverberation [6], [7].…”
Section: Introductionmentioning
confidence: 99%